Comparison of Self-Esteem in Patients Before and after Chemical Skin Peeling: An Interventional Study - Rasheed, Maria; Zulfiqar, Sumeera; Bari, Ahsan; Zainab, Alina (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the self-esteem of patients undergoing chemical peeling for therapeutic reasons. Study Design: Pre-post Observational study. Place and Duration of Study: Department of Dermatology Combined Military Hospital, Multan Pakistan, from Mar to Aug 2021. Methodology: Forty-four patients were included in the study. After detailed history and clinical examination, self-esteem of all selected patients meeting the inclusion criteria was determined using RSES (Rosenberg Self-Esteem Score) score. Four sessions of chemical peeling were done using 30% salicylic acid with interval of 2 weeks between each session. (At week 0, 2, 4 and 6) All patients were advised the use of similar sun blocks during the treatment period. Post-peel RSES was re-assessed at 6 weeks. Results: The pre-peel RSES score (17.95±2.29) improved significantly after the sessions of chemical peeling. The post-peel RSES score was (19.47±1.95). p-value<0.001 Conclusion: Our study showed chemical peeling with 30% salicylic acid caused a significant enhancement of patients’ self- esteem, as significant difference in Rosenberg Self-Esteem Scores was seen before and after chemoexfoliation.